BERBAGI PENGETAHUAN DAN PENGARUHNYA PADA KEMAMPUAN INOVASI INDUSTRI RUMAH TANGGA DI SULAWESI UTARA: SEBUAH STUDI LONGITUDINAL - Senduk, Ventje A; Wuryaningrat, Nikolas F (Jurnal MS, 2014)
resources is through the sharing of knowledge . Sharing knowledge becomes an integral part to the company according to Argote et al. (1999 in Srivastava et al, 2006) is a way to share the knowledge of how to optimize enterprise knowledge resources to be used for the improvement of innovation capability . The big difference in the results of research it is necessary to study more in-depth . Research that has been described only focus of research with a cross-sectional manner . The research was conducted by means of a longitudinal study to provide a more comprehensive understanding . The results of research on the time period of the first survey revealed that knowledge sharing is not a member of influence on innovation capability indistri home date in North Sulawesi. Along with the learning process of knowledge sharing members a significant effect on the ability of innovation . Â